Fracture behavior of all-ceramic, implant-supported, and tooth-implant-supported fixed dental prostheses - Alkharrat, Abdul Rahman; Rues, Stefan (Clinical oral investigations, 2017)
OBJECTIVES: In vitro investigation of the effects of fixed dental prosthesis (FDP) support and loading conditions on the fracture behavior of all-ceramic, zirconia-based FDP veneered with computer-aided design/computer-aided manufacturing (CAD/CAM)-manufactured lithium disilicate ceramic. MATERIALS AND METHODS: Based on a model for a 3-unit FDP in the molar region (tooth in region 15, implant in region 17), 16 identical zirconia frameworks were fabricated and veneered with milled lithium disilicate ceramic. Another 16 FDPs were manufactured similarly, using a model in which the tooth was replaced by an implant. The specimens underwent 10,000 thermal cycles between 6.5 and 60 °C and 1,200,000 chewing cycles with a force magnitude of 100 N. All were then subsequently loaded until fracture in a universal testing device. Half of the FDPs were subjected to centric and axial loading on the pontic, the others to eccentric and oblique loading on one cusp of the pontic. RESULTS: No failures were observed after artificial aging. Fracture loads of tooth-implant-supported restorations were 1636 ± 158 and 1086 ± 156 N for axial and oblique loading, respectively; implant-supported FDPs fractured at 1789 ± 202 and 1200 ± 68 N, respectively. Differences were significant for load application (P < 0.001) and support type (P = 0.020). For the two types of load application, fracture mode differed substantially: complete fracture was observed for centric and axial loading whereas mixed cohesive/adhesive failure was observed for many FDPs loaded eccentrically and obliquely. CONCLUSIONS: The high incidence of chipping of manually veneered implant-supported all-ceramics restorations might be reduced by use of CAD/CAM-manufactured lithium disilicate veneers. CLINICAL RELEVANCE: FDPs veneered with lithium disilicate resist occlusal forces of 500 N, irrespective of load application and support type. The fracture resistance of implant-supported FDPs was, however, higher than that of combined tooth-implant-supported FDPs. Their clinical use seems to be justified.